Protective effect of the combination of essential oil from patchouli and tangerine peel against gastric ulcer in rats. (10th January 2022) - Chen, Guanru; Xie, Xiaofang; Peng, Fu; Wang, Tianzhixin; Chen, Junren; Li, Gangmin; Liu, Juan; Peng, Cheng
Abstract: Ethnopharmacological relevance: Essential oil (EO) is the main extract of patchouli and tangerine peel with antiinflammatory, antiulcer, and other functions. However, the efficacy and mechanism of the combination of EO from patchouli and tangerine peel against gastric ulcer (GU) are unclear. Aim of the study: This study aims to reveal the protective effect of the combination of EO from patchouli and tangerine peel against GU in rats, as well as explore the optimal ratio and possible mechanism of EO in GU treatment. Materials and methods: The GU model is executed via water immersion and restraint stress. The repair effect of EO in different proportions on gastric mucosa injury and the effects on serum gastrin (GAS), pepsinogen C (PGC), prostaglandin E2 (PGE2), and 5-hydroxytryptamine in GU rats were observed. The optimal ratio obtained was used in the second part to set different dose groups for further experiment. The effects of the different EO doses on gastric mucosal ulcer formation and gastric acid secretion were evaluated. The morphology of chief and parietal cells were observed via transmission electron microscopy. The contents of GAS, PGC, substance P (SP), cyclic adenosine monophosphate (cAMP), cyclic guanosine monophosphate (cGMP), cholecystokinin (CCK), PGE2, and motilin (MTL) in serum in different groups were detected via enzyme-linked immunosorbent assay. Expressions of epidermal growth factor (EGF) and trefoil factor 2 (TFF2) protein in gastric tissues were detected via immunohistochemistry, and expressions of c-Jun N-terminal kinase (JNK), P53, Bcl-2-associated X protein (Bax), and Caspase-3 protein in gastric tissues were detected via western blotting. Results: The EO from patchouli and tangerine peel at 1:2 ratio of compatibility significantly improved gastric mucosal injury, decreased serum GAS and PGC contents, and increased the PGE2 level in serum ( p  < 0.05). The mixture of EO from patchouli and tangerine peel (Mix-EO) can reduce the formation of gastric mucosal ulcers, reduce gastric mucosal injury, improve the expansion of the endoplasmic reticulum of the chief cells, repair mitochondrial damage, and inhibit the secretion of gastric acid by parietal cells. Mix-EO at 300 mg/kg can reduce the expression of serum GAS, PGC, SP, CCK, and cAMP/cGMP ( p  < 0.05 or 0.01); increase the expression of EGF and TFF2 protein in gastric tissues ( p  < 0.01); and inhibit the expression of JNK, p53, Bax, and Caspase-3 proteins ( p  < 0.01). Conclusion: The combination of EO from patchouli and tangerine peel can repair the gastric mucosal damage in GU rats and prevent the occurrence of ulcers by inhibiting the secretion of gastric acid, enhancing the defensive ability of gastric mucosa, and suppressing the apoptosis of gastric epithelial cells. Moreover, the optimal compatible ratio of patchouli and tangerine peel is 1:2. Graphical abstract: Image 1